Recent research developments in polymer heat exchangers – A review. (July 2016) - Chen, Xiangjie; Su, Yuehong; Reay, David; Riffat, Saffa
Abstract: Due to their low cost, light weight and corrosive resistant features, polymer heat exchangers have been intensively studied by researchers with the aim to replace metallic heat exchangers in a wide range of applications. This paper reviews the development of polymer heat exchangers in the last decade, including cutting edge materials characteristics, heat transfer enhancement methods of polymer materials and a wide range of polymer heat exchanger applications. Theoretical modelling and experimental testing results have been reviewed and compared with literature. A recent development, the polymer micro-hollow fibre heat exchanger, is introduced and described. It is shown that polymer materials do hold promise for use in the construction of heat exchangers in many applications, but that a considerable amount of research is still required into material properties, thermal performance and life-time behaviour.